Impact of hydraulic interventions on chronic and acute material loading and discolouration risk in drinking water distribution systems. (1st February 2020) - Sunny, I.; Husband, P.S.; Boxall, J.B.
Abstract: This paper presents results from an intensive long term investigation in three comparable trunk mains and downstream impact of non-invasive, in-service flow conditioning to manage discolouration risk. Findings show that flow conditioning, the careful regular increase in flows to mobilise small amounts of material from cohesive layers formed at the pipe wall, provides immediate risk mitigation and system resilience benefits. Evidence is presented showing longer term risk reduction in the trunk mains and a 25% discolouration risk reduction in the downstream networks. Whilst the flow conditioning produced an acute but short duration controlled mobilisation of material from the trunk main, longer term downstream monitoring showed reduced chronic or background material loading. It is proposed this change is due to altering the material exchange behaviour and volumes bound within cohesive layers that develop on bulk water/infrastructure interfaces. The paper provides evidence that flow conditioning is an efficient strategy to manage discolouration risk and improve consumer water quality throughout water distribution systems. Graphical abstract: Image 1 Highlights: Hydraulic management provides water quality risk mitigation and network resilience. Chronic material load is more significant for discolouration risk than acute events. Flow conditioning can reduce downstream chronic material load. Flow conditioning is an effective and sustainable tool to manage discolouration.